2001
DOI: 10.1006/eesa.2000.2032
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic and Behavioral Neurotoxicity of Carbaryl and Cadmium to Larval Rainbow Trout (Oncorhynchus mykiss)

Abstract: Pesticides and heavy metals are common environmental contaminants that can cause neurotoxicity to aquatic organisms, impairing reproduction and survival. Neurotoxic effects of cadmium and carbaryl exposures were estimated in larval rainbow trout (RBT; Oncorhynchus mykiss) using changes in physiological endpoints and correlations with behavioral responses. Following exposures, RBT were videotaped to assess swimming speed. Brain tissue was used to measure cholinesterase (ChE) activity, muscarinic cholinergic rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 30 publications
7
42
0
Order By: Relevance
“…ATPase causing metabolic effects and disrupting neurotransmitter uptake [45]. In several situations, acetylcholine is not broken and accumulates within synapses causing physiologic impairment and alterations in fish swimming behavior [46] It is clear from the present study that the toxicity of metal is affected by Ca which in turn reduces the toxic effect of metal through competitive inhibition at the gill surface.…”
Section: Discussionmentioning
confidence: 83%
“…ATPase causing metabolic effects and disrupting neurotransmitter uptake [45]. In several situations, acetylcholine is not broken and accumulates within synapses causing physiologic impairment and alterations in fish swimming behavior [46] It is clear from the present study that the toxicity of metal is affected by Ca which in turn reduces the toxic effect of metal through competitive inhibition at the gill surface.…”
Section: Discussionmentioning
confidence: 83%
“…This possibly explains why past studies have suggested that Cd does not alter normal fish behaviour by disrupting brain function (e.g. neurotransmitter levels; Beauvais et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although herbicides could indirectly affect salmonids via effects to algae and plants, direct effects to fish from these pesticides are much less likely. In contrast to the other pesticide groups, carbamates and organophosphate pesticides are highly toxic to salmonids (Beauvais et al 2000(Beauvais et al , 2001Sandahl and Jenkins 2002;Sandahl et al 2005;Laetz et al 2009;NOAA 2009) and were frequently detected in the Washington State WRIAs from 2003 to 2007. Thus, carbamate and organophosphate pesticides are the pesticides of greatest concern for direct effects to Pacific salmonids.…”
Section: The Washington State Monitoring Studymentioning
confidence: 99%
“…Inhibition of AChE activity occurs in the central nervous system (CNS) and in the plasma and muscle of fish (Perkins and Schlenk 2000). Studies with a number of carbamate and organophosphate pesticides (e.g., azinphosmethyl, chlorpyrifos, malathion, diazinon, carbaryl) have demonstrated an association between inhibition of brain AChE activity and behavioral endpoints such as reduction in spontaneous swimming and feeding rates, swimming stamina, predator detection, and homing behavior (Post and Leasure 1974;Moore and Waring 1996;Van Dolah et al 1997;Beauvais et al 2000Beauvais et al , 2001Scholz et al 2000;Sandahl et al 2005;Labenia et al 2007).…”
Section: Toxicity Of Carbamates and Organophosphatesmentioning
confidence: 99%